2011
DOI: 10.14693/jdi.v18i2.61
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Risk Factors and Musculoskeletal Impairment in Dental Students: a Preliminary Study

Abstract: Musculoskeletal disorders are common among dentists, 80% of the measurement results using the instrument of Body Discomfort Map and Brief Survey in Faculty of Dentistry University of Indonesia (FKG UI) showed that musculoskeletal disorders (MSD) mainly occur in the neck, shoulder, forearm, hand and back. MSD are the most common type of occupational dental diseases in Indonesia. Objectives: To know the risk factors associated with MSD in students in FKG UI. Methods: This type of observational study with cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 3 publications
0
7
0
5
Order By: Relevance
“…2 From these data, it can be said that the prevalences of musculoskeletal disorders are high among dentists in some countries. In Indonesia, the prevalence of musculoskeletal disorders is still unknown since there have been no data on the prevalence of musculoskeletal disorders among dentists in Indonesia, especially in the city of Surabaya.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 From these data, it can be said that the prevalences of musculoskeletal disorders are high among dentists in some countries. In Indonesia, the prevalence of musculoskeletal disorders is still unknown since there have been no data on the prevalence of musculoskeletal disorders among dentists in Indonesia, especially in the city of Surabaya.…”
mentioning
confidence: 99%
“…However, based on screening results conducted in Faculty of Dentistry, Universitas Indonesia using Discomfort Body Map and Brief Survey instruments, there are 80% dentists working in clinics suffering from MSD mainly on neck, shoulders, forearms, hands, and back. 2 One of factors causing musculoskeletal syndrome suffered by dentists is that they care more with the comfort for patients treated, but less attention to their comfort when caring for patients. Dentists consider more on the need to move toward their patients rather than to adjust the seating position of their patients on dental chair.…”
mentioning
confidence: 99%
“…2 In Indonesia, the number of incidents is unidentified since there has been no data provided about the prevalence of musculoskeletal complained by dentists in Indonesia According to the result of screening conducted at Faculty of Dentistry, Universitas Indonesia using body discomfort map and brief survey as instruments, which found that 80% of dentists who work in the clinic experience musculoskeletal disorder, particularly on neck, shoulders, forearms, upper arms, hands and back. 2 One of the causes of musculoskeletal syndrome experienced by dentists is because the dentists assume that they are the one who should make moves to get close to the patients rather than they should arrange patient's sitting position on the dental chair. Most musculoskeletal disorders among dentists occur since the dentists are positioning their body unconsciously that do not support their movement during treating the patients.…”
Section: Introductionmentioning
confidence: 99%
“…World Health Organization (WHO) define the MSDs is the disturbance of the muscles, tendons, joints, vertebrae, peripheral nerves and vascular system occur suddenly or gradually and acute and chronic (Wijaya et al, 2011). Adverse impact of the disturbance will result in reduced skills to carry out the work, reduced work productivity and increased health care costs.…”
Section: Introductionmentioning
confidence: 99%